Effects on suicidal risk: Comparison of clozapine to other newer medicines indicated to treat schizophrenia or bipolar disorder. (September 2021) - Forte, Alberto; Pompili, Maurizio; Imbastaro, Benedetta; De Luca, Gabriele Pasquale; Mastrangelo, Martina; Montalbani, Benedetta; Baldessarini, Ross J
Background: Clozapine is the only treatment with regulatory-recognition of lowering suicidal risk, at least in schizophrenia patients. It remains uncertain whether such effects extend to other drugs for psychosis. Methods: We searched for reports on rates of suicidal behavior during treatment with clozapine and other modern drugs for psychosis (aripiprazole, olanzapine, risperidone, quetiapine, and ziprasidone) versus comparison or control treatments and analyzed the contrasts by random-effect meta-analysis to obtain pooled odds ratios (ORs) with 95% confidence intervals (CIs). Results: We identified 35 paired comparisons of modern drugs for psychosis versus comparison or control treatments in 18 reports. There was moderate overall superiority of all agents tested over alternatives (OR = 0.522, p = 0.004). With clozapine, this effect was large (OR = 0.229, p < 0.0001) and consistent (7/7 trials), but significant antisuicidal effects were not found with other drugs for psychosis in 28 other trials (OR = 0.941, p = 0.497). Apparent efficacy of specific agents ranked: risperidone ⩾ olanzapine ⩾ aripiprazole ⩾ ziprasidone ⩾ mixed drugs for psychosis ⩾ quetiapine, but none of these differences was significant. Conclusions: An ability of clozapine to reduce risk of suicides and attempts in schizophrenia patients appears to be a unique effect not shared with other modern medicines indicated for schizophrenia or bipolar disorder.